2003
DOI: 10.1128/aem.69.4.2110-2115.2003
|View full text |Cite
|
Sign up to set email alerts
|

P1 Trisaccharide (Galα1,4Galβ1,4GlcNAc) Synthesis by Enzyme Glycosylation Reactions Using Recombinant Escherichia coli

Abstract: The frequency of Escherichia coli infection has lead to concerns over pathogenic bacteria in our food supply and a demand for therapeutics. Glycolipids on gut cells serve as receptors for the Shiga-like toxin produced by E. coli. Oligosaccharide moiety analogues of these glycolipids can compete with receptors for the toxin, thus acting as antibacterials. An enzymatic synthesis of the P1 trisaccharide (Gal␣1,4Gal␤1,4GlcNAc), one of the oligosaccharide analogues, was assessed in this study. In the proposed synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Phylogenetic analyses revealed some apparent differences in the shallow versus deep denitrifying communities, with certain clusters dominated by sequences from shallow stations, while others by sequences from the deeper stations (Figure 5). As suggested in other studies (Liu et al, 2003; Dang et al, 2009), such a clustering pattern could result from the adaptation of specific denitrifying communities to different environmental conditions that vary with water depth, such as oxygen, carbon, and nitrate availabilities.…”
Section: Discussionsupporting
confidence: 60%
“…Phylogenetic analyses revealed some apparent differences in the shallow versus deep denitrifying communities, with certain clusters dominated by sequences from shallow stations, while others by sequences from the deeper stations (Figure 5). As suggested in other studies (Liu et al, 2003; Dang et al, 2009), such a clustering pattern could result from the adaptation of specific denitrifying communities to different environmental conditions that vary with water depth, such as oxygen, carbon, and nitrate availabilities.…”
Section: Discussionsupporting
confidence: 60%
“…9,10 Thus, Wang's group already showed that enzymatic synthesis of the P1 trisaccharide (Gala1,4Galb1,4GlcNAc), an oligosaccharide analogue, was assessed with H. pylori b1,4-GalT and Neisseria meningitides a1,4-GalT. 11 Those studies provide an efficient approach, including the substrate flexibility of b1,4-GalT, for the galactosylation of other molecules. In addition, the Pm0188 gene from P. multocida has been cloned, and a truncated protein (tPm0188Ph) was expressed in E. coli.…”
Section: Udp-mentioning
confidence: 99%
“…23 Enzymatic effect of b-1,4-GalT and a-2,3 Sia T in NeuAca2,3-Gal b-1,4 GlcNAc Protocols used to enzymatically synthesize Galb1,4-GlcNAc (4) and NeuAca2,3 Galb1,4-GlcNAc (5) using b1,4-GalT and a2,3-SiaT were performed as published elsewhere. 11,12,24 Compound 3 was tested in an enzymatic reaction with b1,4-GalT in an attempt to prolong the production of 4. The galactosylation reaction was performed with 50 mM HEPES, pH 7.6, 1.0 mM MnCl 2 , 40 mM 3, 20 mM UDP-Gal and 100 mM purified b1,4-GalT.…”
Section: Expression and Purification Of B14-galt And A23-siatmentioning
confidence: 99%
See 1 more Smart Citation
“…The values are given as s -1 . ** Hydrolytic activity using 2.6 mM X 3 . The values are given as s -1 .…”
Section: E Conversion Of Rex Into Glycosynthase E-1 Hehre Resynthesmentioning
confidence: 99%